A study of kitsch in South African suburban society - Page, Lindsay Ann (Rhodes University, Faculty of Humanities, Department of Fine Art, 1984)
Consider the possibility of the remnants of our present day society being excavated and studied in centuries to come. Imagine the craftsmanship, the art, artifacts and architecture that will then be compared to those of the past centuries. Our entire culture will be labelled by the endless array of rubbish that has become an integral part of our lives. The increasing prevalence of kitsch in the society goes almost unnoticed where it should be causing concern. Few people are aware of its existence, or the permanent aesthetic scars induced by this prevalence. How has this cult of sheer awfulness come about and why has it become prevalent? It is impossible to pursue all the avenues of kitsch - so vast is it but it is the purpose of this study to try and answer some of the questions, in order to make people more aware of what has crept into our society, to help them become more discriminating, and not merely to level criticism at the perpetrators of kitsch.
Keywords: Kitsch -- South Africa; Decorative arts -- South Africa; Popular culture -- South Africa